THE STATE OF JUVENILE DELINQUENCY IN THE ALMATY CITY (Journal of actual problems of jurisprudence, 2018)
Even children can face the law. Once this happens, and the child enters the criminal justice system, he or she can be considered a “minor offender”. The problem of juvenile delinquency remains relevant in Kazakhstan. In this article, as a method of investigating juvenile delinquency, statistics and dynamics of the city of Almaty use juvenile delinquency. The author begins the study with the main statistics of growth or decrease in the number of crimes committed by minors, by region. The author also analyzes the dynamics of growth and the reduction in the number of juvenile delinquencies using the diagram from 2012 to 2017 and explains the main reasons for the growth or decrease in collic crime in certain years. The author also provides kollichestvennuyu statistics in the form of a table of perfect types of crimes by minors from 2012 to 2016, and analyzes the reason why some types of crimes are so often committed by juveniles. In this article, we analyze in various ways in which area of Almaty the crime among minors, the identity of the offender and in what form the crime among minors (for example, group form) is committed. In the article some questions are investigated why minors fall into the path of crime and how their environment affects them, and also how to prevent crime among minors.Key words: juvenile delinquency, prevention of offenses, combating juvenile delinquency.